Regional library infrastructure management for service improvement in Bangka Belitung Islands Province - Hamudy, Moh Ilham A; Rifki, M Saidi; Hayuningtyas, Mukhlisha (Universitas Padjadjaran, 2024)
The Archives and Library Service office of Bangka Belitung Islands (Babel) Province has a vital role in increasing literacy and reading interest in the community. Library users can access library services through the provision of infrastructure that suits the needs of library users. Infrastructure management is carried out to enhance services to library users. This study aims to determine the management of regional library infrastructure for service improvement in Babel Province through infrastructure analysis to enhance literacy and interest in reading, budget management, and human resource competency. This research method used was descriptive qualitative. The results indicated that the Archives and Library Service office of Babel Province had inadequate facilities and infrastructure, such as outdated book collections, poorly maintained shelves and reading tables, and less than optimal circulation facilities. The library has not prioritized budget management related to the procurement of facilities and infrastructure, and human resource competencies resources are not optimal in budget planning and management. The library has not conducted a comprehensive user survey, thus hindering the analysis of user needs and providing service facilities that have not met community expectations. The study concludes that infrastructure and budget planning at the Bangka Belitung Provincial Archives and Library Office has not been implemented optimally, thus obstructing the provision of library services and having an impact on low literacy and reading interest among people in the area.